Термодинамический анализ возможного взаимодействия алмаза и инструмента с горными породами - Кухаренко, С.А.; Шило, А.Е.; Довгань, А.Г. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The results of the thermodynamic analysis of possible interaction of diamond and components of the metallic bond of diamond tool with the rocks are given. The influence of the chemical composition of the rocks on the possible wear of diamond tool is shown.